Evaluating the efficacy of RT-qPCR SARS-CoV-2 direct approaches in comparison to RNA extraction. (October 2020) - Israeli, Ofir; Beth-Din, Adi; Paran, Nir; Stein, Dana; Lazar, Shirley; Weiss, Shay; Milrot, Elad; Atiya-Nasagi, Yafit; Yitzhaki, Shmuel; Laskar, Orly; Schuster, Ofir
Highlights: The genetic identification of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is based on viral RNA extraction prior to RT-qPCR assay, however recent studies, using different buffers, support the elimination of the extraction step (direct approaches). We obtained similar limit of detection levels for SARS-CoV-2 when analyzing laboratory (non-clinical) samples using viral RNA extraction prior to RT-qPCR assay and direct approaches. However, in clinical oro-nasopharyngeal SARS-CoV-2 swabs, there was an advantage for the extraction procedure. Although previously reported to facilitate viral detection, the buffers tested here severely compromised the level of detection of clinical samples. A direct no-buffer approach might be an alternative, in times of need, since it identified more than 60% of positive clinical specimens. Abstract: The genetic identification of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is based on viral RNA extraction prior to RT-qPCR assay. However, recent studies have supported the elimination of the extraction step. This study was performed to assess the necessity for the RNA extraction, by comparing the efficacy of RT-qPCR in several direct approaches versus the gold standard RNA extraction, in the detection of SARS-CoV-2 in laboratory samples, as well as in clinical oro-nasopharyngeal SARS-CoV-2 swabs. The findings showed an advantage for the extraction procedure; however a direct no-buffer approach might be an alternative, since it identified more than 60% of positive clinical specimens.